Pregabalin alleviates neuropathic pain via inhibition of the PKCε/TRPV1 pathway. (1st January 2022) - Zhang, Xiaoyu; Peng, Lihua; Liu, Danyan
Highlight: Pregabalin alleviates the hyperalgesia induced by SNI. Pregabalin decreases the expression of IL-1β and IL-6 in SNI rats. Pregabalin significantly reduces the level of PKCε/TRPV1 and reactive astrocytes in SNI rats. Abstract: Pregabalin has been increasingly used in recent years, and becoming a first-line medication for the clinical treatment of neuropathic pain. However, the mechanisms underlying pregabalin-induced neuropathic pain alleviation remain unclear. In this study, we aimed to investigate whether PKC epsilon (PKCε)/ transient receptor potential vanilloid subtype 1(TRPV1) signaling pathway participated in pregabalin-induced analgesia during treatment of neuropathic pain using rat models of spared nerve injury (SNI). The left hind paw withdrawal mechanical thresholds (PWMT) of rats were measured preoperatively one day before and on day 1, 4, 7 and 14 after surgery. On day 7 after SNI surgery, the rats received ligation operation were administrated with pregabalin intraperitoneally and were intrathecally injected with PKC Inhibitor BIM Ⅰ or PKC agonist PMA for seven consecutive days, IL-1β and IL-6 expression levels in the spinal cord of rats were then assessed. Furthermore, we analyzed the PKCε, TRPV1, pTRPV1 and Glial fibrillary acidic protein (GFAP) protein levels and the expression of reactive astrocytes and the PKCε, TRPV1 and pTRPV1 positive cells on day 14 after SNI. Our findings indicated that pregabalin could relieve neuropathic pain to a certain extent by suppressing the PKCε/TRPV1 signaling pathway and inhibiting inflammatory processes in the spinal cord.